SYNTHESIS AND OPTIMIZATION OF CARBON NANOPARTICLES (C-DOTS) AS ABSORBER MATERIALS FOR SOLAR DISTILLATION APPLICATIONS (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
Carbon nanoparticles (C-Dots) were synthesized using citric acid and urea as carbon and fuel source, and combustion reaction methods. The absorption spectral and morphology particles of C-Dots were investigated. The morphology describes the synthesis of small (1 ?m) and monodispersedC-Dots. Thus, the C-Dots solutions has absorption spectral range of about 86% at visible light spectral. This study suggests that the as-prepared carbon nanoparticles (C-Dots) with particle size and absorption spectral tunability might be utilized as solar energy absorber material.Karbon nanopartikel (C-Dots) disintesis menggunakan asam sitrat dan urea sebagai sumber karbon dan bahan bakar, melalui reaksi pembakaran sederhana. Spektrum absorpsi dan morfologi partikel C-Dots diinvestigasi menggunakan UV-Vis Spectrometry dan analisis SEM. Hasil SEM menunjukan bahwa morfologi partikel C-Dots sangat kecil (1 ?m) dan seragam. Selain itu, larutan C-Dots memiliki spektrum absopsi pada rentang sekitar 86% pada daerah cahaya tampak. Hasil studi ini menunjukan bahwa karbon nanopartikel (C-Dots) dengan ukuran partikel dan spektrum absorpsi yang dapat diatur, sehingga dapat digunakan sebagai material penyerap sinar matahari.